Chaotic Based Asymmetric and Symmetric Key Encryption Using Augmented Lorenz Equations - Josy Elsa Varghese, Winnie Sara Simon (International Journal of Scientific Research and Management (IJSRM), 2015)
In the proposed paper, a comparison on the asymmetric key cryptographic system and the symmetric key cryptographic system over augmented Lorenz equations is conducted. In asymmetric secret key system, at both sender side and the receiver side, the corresponding private key, public key and the secret key are generated. The chaotic signal for encryption and decryption are generated at the sender and the receiver from augmented Lorenz equations using the corresponding secret keys which are generated at the sender and the receiver. The cipher text is therefore generated by applying XOR function between the chaotic signal and the plain text. The plain text can be extracted from the received cipher text by again applying XOR function between the chaotic signal and the cipher text. In symmetric secret key system, a shared secret key is generated for the sender and the receiver using the QKD protocol. The shared secret key is used for generating chaotic signal from augmented Lorenz equations at both sender side and the receiver side. The chaotic signal is then masked with the plain text to obtain the cipher text. Consequently at the receiver side, the regenerated chaotic signal is unmasked from cipher text to obtain the plain text.